Stigmatizing Street Children in Surabaya: A Systemic Functional Linguistics Perspective - Syafa Nameyra Eka Nofitri; Fariq Shiddiq Tasaufy (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2026)
In Indonesian public discourse, street children are frequently associated with criminality, disruptive behavior, and social deviance. However, the linguistic mechanisms that produce and normalize this type of stigma are poorly understood. This study investigates how social actors in Surabaya depict street children linguistically in spoken interactions. Ten informants were drawn from three community groups: institutional stakeholders, community representatives, and civil society actors. They participated in semi-structured interviews to collect qualitative data. The data were then analyzed using an integrated framework of systemic functional linguistics and stigma theory. The findings show that street children are most frequently portrayed through relational processes (26.7%), encoding negative qualities as fixed inherent traits, followed by mental processes (23.3%) that frame them as cognitively and emotionally deficient. In terms of evaluation, judgment resources predominate (70%), with stigmatizing social scripts being reproduced by negative evaluations of normality and propriety. Stereotyping is the most prevalent of Link and Phelan's (2001) stigma components (46.7%), which is achieved by the co-occurrence of relational processes and monoglossic judgment. This study offers a novel contribution by combining transitivity, appraisal, and stigma theory in the analysis of grassroots spoken discourse on marginalized groups in Indonesia. The findings imply that stigma is maintained by normalized patterns of everyday language in addition to overt animosity.